Antibacterial activity of turmeric (Curcuma longa) extract against staphylococcus aureus and escherichia coli / Nur'alin Syahmina Hashim and Latifah Munirah Bakar - Hashim, Nur'alin Syahmina; Bakar, Latifah Munirah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Foodborne pathogens, such as Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli), are known to cause a wide range of illnesses and are typically found in contaminated food. S. aureus is a Gram-positive bacterium, while E. coli is a Gram-negative bacterium. This study aimed to assess the antibacterial activity of turmeric (C. longa) extract against these common foodborne pathogens, S. aureus, and E. coli. Turmeric extract demonstrated effective antibacterial properties against both bacteria. The foodborne pathogens were tested using the disc diffusion method, with the lowest concentration starting at 100 mg/mL, which showed a mean inhibition zone of more than 9 mm for both S. aureus and E. coli. The highest concentration tested was 500 mg/mL, which showed a mean inhibition zone of more than 10 mm for both bacteria. The minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) for these bacteria were found to be around 100 μg/mL. The disc diffusion method revealed that concentrations ranging from 100 mg/mL to 500 mg/mL inhibit the bacterial growth, and the percentage inhibition of diameter growth (PIDG) results confirmed significant inhibition. The PIDG of S. aureus was positive and increased as the concentration increased, while E. coli showed a negative correlation between PIDG and concentration increase. These findings support the presence of antibacterial properties in turmeric rhizome (Curcuma longa) and its potential as a natural means to combat foodborne pathogenic bacteria.